2020
DOI: 10.1080/16078454.2020.1850973
|View full text |Cite
|
Sign up to set email alerts
|

The role of cystatin C as a proteasome inhibitor in multiple myeloma

Abstract: Objectives: Bone destruction and renal impairment are two frequent complications of multiple myeloma (MM). Cystatin C, an extracellular cysteine proteinase inhibitor, is encoded by the housekeeping gene CST3 and associated with human tumors. The role of cystatin C in multiple myeloma has been revealed recently. The purpose of this study was to explore the role of cystatin C as a proteasome inhibitor in multiple myeloma. Methods: A comprehensive literature review was conducted through Pubmed to summarize the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Cystatin C (Cys-C) is a cysteine protease inhibitor that is distributed in various body fluids such as blood and cerebrospinal fluid, and its production is not affected by other physical characteristics or external conditions [ 5 ]. One study [ 6 ] noted that a significant increase in Cys-C levels could be observed in the serum of patients with AKI and correlated with the severity of kidney damage.…”
Section: Introductionmentioning
confidence: 99%
“…Cystatin C (Cys-C) is a cysteine protease inhibitor that is distributed in various body fluids such as blood and cerebrospinal fluid, and its production is not affected by other physical characteristics or external conditions [ 5 ]. One study [ 6 ] noted that a significant increase in Cys-C levels could be observed in the serum of patients with AKI and correlated with the severity of kidney damage.…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, the main treatment methods for the MM include symptomatic support therapy, high-dose chemotherapy, bone marrow hematopoietic stem cell transplantation, and cellular immunotherapy [ 5 , 6 ]. In the past decade or so, the selective protease inhibitors (such as bortezomib and carfilzomib) and immunomodulatory drugs (such as lenalidomide) have been widely used, although the median survival period of patients can be extended to six years, but at the same time, the high cost has also increased the financial burden of patients and even caused some patients to refuse treatment [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it has been associated with poor prognosis of patients with MM [ 20 ]. Furthermore, there is also increasing evidence that CysC may be associated with bone disease in MM, and it has been proposed as a biomarker and, further, as a potential therapeutic target in this type of cancer [ 13 , 21 ]. CysC has also been shown to identify a subset of ISS-3 score patients with worse outcome [ 13 ].…”
Section: Discussionmentioning
confidence: 99%